Strengthening adoption pathways for improved bean varieties through public private partnerships with grain buyers and seed producers - Kadege, Edith L; Ochieng, Justus; Fayu, Alexandar; Radegunda, Kessy; Mwakatwila, Atupokile; Chima, Rickards; Kibaraza, Areth; Minayo, Davine; Kalemera, Sylvia M; Rubyogo, Jean Claude (2025)
Grain traders are essential actors in the seed value chain, linking seed producers, agro-dealers, and farmers to ensure timely access to quality seeds. They facilitate distribution across regions, provide market information on demand and preferred varieties, and help maintain seed quality during storage and transport. In both formal and informal systems, traders influence varietal choice and seed demand through their grain purchasing preferences, which shape farmers’ production decisions. Experiences from the ACCELERATE project demonstrate how strategic partnerships among Tanzania Agricultural Research Institute (TARI), seed producers, and grain off takers in strengthens seed and grain linkages and transform business in Tanzania and beyond. These collaborations have improved access to certified seed, addressed grain quality challenges, and created opportunities for early generation seed production and variety improvement. With technical support from Tanzania Official seed certification Institute (TOSCI), this trader-led model enhances seed system efficiency, boosts market competitiveness and offers a scalable pathway for increasing productivity, income and food security for smallholder farmers.